Development of site-specific allometric equation for estimating biomass of mixed mature mangrove forest at Sungai Pulai Reserve Forest Gelang Patah, Johor - Muhammad, Muhammad Sofee (2018)
Allometric equations are normally established for estimating aboveground tree biomass and others tree part biomasses in order to avoid any destructive samplings in the future. However, the establishment of site specific allometric equations is needed to estimate accurately the tree biomass in an area. Two compartments were chosen in mixed mature, compartment 16 and 421B, Sungai Pulai Forest Reserve, Gelang Patah, Johor by using judgement sampling method and 1 ha of four inventory plots (50m x 50m) was established in each compartment. Diameter at breast height (D) and height (H) of each individual tree in the plot were taken. Species was identified and grouped based on different diameter classes. The establishment of site-specific equation was done by destructively sampling of 30 trees. Weighing and recording of fresh sample data were done in-situ. 100 gram of fresh sample for plant part; leaves, stems, branch and twigs were collected and brought back to the laboratory for oven-dry process and dry weight was calculated. Five allometric equations comprising independent variables D, H as well as wood specific gravity (p) were derived by using power function model and compared to the best fit model for aboveground mangrove biomass (M) with published common equation. Regression analysis revealed that the coefficient of determination (R2) ranged from 0.6333 to 0.9429 for model using D and ranged from 0.6336 to 0.9481 by using model D2H. However, model using D and p gives R2 value at 0.9579. The results of correlations between observed and predicted values showed that eq (5) using p parameter was likely yield greater r-square values (0.958) compared to Eq. (1) using D (R 2=0.9428), Eq (2) using D2H component (R2=0.9481), Eq (3) using D Total (R2=0.9429) and eq (4) using D2H Total with (R2=0.9481). Simulation of each model (equation) was also made to the 1400 individual data comprising different tree species from tree census. Comparison of wood specific gravity (p) parameter and other develop models as shown by eq (5) (p and D) was found to be accurate which is the value near to 1 (0.9983). Therefore, quadratic of (p and D) found to be the best model for estimating aboveground biomass in this mangrove forest. This finding also revealed that the small number of samples could be reliable if the wood density or wood specific gravity is included in the model for estimating the aboveground biomass of mangrove species.